2017
DOI: 10.1007/978-3-319-47810-4_14
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Memories in Transient Networks

Abstract: Spatial awareness in mammals is based on an internalized representation of the environment, encoded by large networks of spiking neurons. While such representations can last for a long time, the underlying neuronal network is transient: neuronal cells die every day, synaptic connections appear and disappear, the networks constantly change their architecture due to various forms of synaptic and structural plasticity. How can a network with a dynamic architecture encode a stable map of space? We address this que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…It is natural to view the coactivity complexes F ( i ) as instances of a single flickering coactivity complex F , F (t i ) = F ( i ), having appearing and disappearing maximal simplexes (see Fig. 2B and [52]). In the following, we will use F as a model of transient cell assembly network and study whether such a network can encode a stable topological map of the environment on the moment-by-moment basis.…”
Section: The Modelmentioning
confidence: 99%
“…It is natural to view the coactivity complexes F ( i ) as instances of a single flickering coactivity complex F , F (t i ) = F ( i ), having appearing and disappearing maximal simplexes (see Fig. 2B and [52]). In the following, we will use F as a model of transient cell assembly network and study whether such a network can encode a stable topological map of the environment on the moment-by-moment basis.…”
Section: The Modelmentioning
confidence: 99%
“…Among other applications, it has been used to determine differences in brain networks of children with hyperactivity disorders and autism spectrum in comparison to normal situations 25 , study the effect of the psychoactive component of "magic mushrooms" (psilocybin mushrooms) on functional brain networks of humans 26 , analyze covariates that influence neural spike-train data 27 , and study structural and functional organization of neural microcircuits 28 . Other neuronal applications have included consideration of place cells in the hippocampus of rats during spatial navigation [29][30][31] , analysis of mathematical models of transient hippocampal networks 32 , and a demonstration that topological features of networks of brain arteries in humans are correlated with their age 33 . We also note that PH is not the only topological method that has been used to study the human brain or time series.…”
Section: Introductionmentioning
confidence: 99%
“…The algebraic-topological properties of the coactivity complexes were studied in Dabaghian et al ( 2012 ), Babichev et al ( 2016b ), and Babichev and Dabaghian ( 2017a , b ). There it was demonstrated that if place cell populations operate within biological parameters, then the number of topological loops in different dimensions of the coactivity complex—the Betti numbers (Munkres, 2000 )—match the Betti numbers of the environment .…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the learning times and other global characteristics of produced via algebraic topology techniques are insensitive to many details of the place cell spiking activity (Dabaghian et al, 2012 ; Babichev et al, 2016b ; Babichev and Dabaghian, 2017a , b ). For example, the learning time T min depends mostly on the mean place field sizes and the mean peak firing rates, but it does not depend strongly on the spatial layout of the place fields or on the limited spiking variations.…”
Section: Resultsmentioning
confidence: 99%